2012
DOI: 10.1016/j.sjbs.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Viral and bacterial infections associated with camel (Camelus dromedarius) calf diarrhea in North Province, Saudi Arabia

Abstract: Diarrhea and deaths in new-born camel calves were noticed by veterinary investigators and pastoralist in Saudi Arabia to be very high. Hence, it is thought to be necessary to investigate this problem from the virological and bacteriological point of view. The role of pathogenic bacteria and viruses in six different towns of North Province (Al-Assafia, Arar, Domat Aljandal, Hail, Skaka and Khoa) in Saudi Arabia was studied. Survey was conducted in diarrheic camel calves aged 12 months or younger. In our study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 12 publications
0
41
0
Order By: Relevance
“…While clinical cases are easy to detect by manual palpation and by visual examination of the milk using a strip cup (there is swelling, heat, pain and in duration in the mammary gland, and the milk is discolored and clotted), a large proportion of mastitis cases are not readily detectable; such cases are referred to as subclinical mastitis. In the latter cases, the diagnosis has become dependent largely on indirect tests which depend in turn on the leucocyte content of the milk [17]. Mastitis is a relatively infrequent disease in camels compared with cattle, but the incidence of mastitis may increase in dairy camels due to hand milking and teat malformation [18].…”
Section: Mastitismentioning
confidence: 99%
“…While clinical cases are easy to detect by manual palpation and by visual examination of the milk using a strip cup (there is swelling, heat, pain and in duration in the mammary gland, and the milk is discolored and clotted), a large proportion of mastitis cases are not readily detectable; such cases are referred to as subclinical mastitis. In the latter cases, the diagnosis has become dependent largely on indirect tests which depend in turn on the leucocyte content of the milk [17]. Mastitis is a relatively infrequent disease in camels compared with cattle, but the incidence of mastitis may increase in dairy camels due to hand milking and teat malformation [18].…”
Section: Mastitismentioning
confidence: 99%
“…The present review focuses on the exotic/unusual rotaviruses detected in livestock (cattle and pigs), horses and companion animals (cats and dogs). Avian RVs (RVD, RVF and RVG), including RVAs, which are genetically Typical RVA VP7 and VP4 genotypes Humans G1-G4, G9, G12, P [4], P [6], P [8] Cattle G6, G8, G10, P [1], P [5], P [11] Pigs G3-G5, G9, G11, P [6], P [7] Horses G3, G14, P [12] Cats and dogs G3, P [3], P [9] Exotic rotaviruses in animals 159 divergent from mammalian RVAs, are also discussed. Although scattered and limited studies have reported rotaviruses in several exotic animals and birds, including wildlife, these data remain to be compiled and reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Exotic/unusual rotaviruses in livestock, horses and companion animals Cattle G6, G8 or G10 RVAs possessing P [1], P [5] or P [11] are commonly found in cattle, with G6P [5] being the most predominant genotype combination among bovine RVAs [22,104] (Table 2). In addition, RVA strains belonging to other VP7 genotypes (G1-G4, G5, G11, G12, G15, G17, G21 and G24) and VP4 genotypes (P [3], P [6], P [7], P [14], P [17], P [21], P [29] and P [33]) have been reported occasionally in cattle [91,104]. Some of these genotypes are commonly detected in human RVAs (G1-G4, G12 and P [6]) and porcine RVAs (G3-G5, G11, P [6] and P [7]), whilst some others are avian-like (G17P [17]) or novel bovine genotypes (G15, G21, G24, P [21], P [29] and P [33]) [80,91,95,104].…”
Section: Introductionmentioning
confidence: 99%
“…The recent emergence of Middle East Respiratory Coronavirus (MERS-CoV) from the Middle East and the presence of neutralizing antibodies against MERS-CoV from dromedaries in the Middle East have boosted interest in the search of novel viruses in dromedaries (de Groot et al, 2013;Lau et al, 2013;Perera et al, 2013;Reusken et al, 2013;Zaki et al, 2012). Viruses of at least eight families, including Paramyxoviridae, Flaviviridae, Herpesviridae, Papillomaviridae, Picornaviridae, Poxviridae, Reoviridae and Rhabdoviridae, have been found to infect camels (Al-Ruwaili et al, 2012;Intisar et al, 2009; Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/yviro Ure et al, 2011;Wernery et al, 2014;Wernery et al, 2008;Wernery and Zachariah, 1999;Yousif et al, 2004). Recently, we have discovered a novel coronavirus, named dromedary camel coronavirus UAE-HKU23 (DcCoV UAE-HKU23), in dromedaries (Woo et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%